2010
DOI: 10.1667/rr1953.1
|View full text |Cite
|
Sign up to set email alerts
|

Non-malignant Thyroid Diseases after a Wide Range of Radiation Exposures

Abstract: Background The thyroid gland is one of the most radiosensitive human organs. While it is well known that radiation exposure increases the risk of thyroid cancer, less is known about its effects in relation to non-malignant thyroid diseases. Objectives The aim of this review is to evaluate the effects of high and low dose radiation on benign structural and functional diseases of the thyroid. Methods We examined the results of major studies from cancer patients treated with high-dose radiotherapy or thyrotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 70 publications
0
38
0
2
Order By: Relevance
“…Ron and Brenner29 summarised the evidence of benign thyroid diseases after radiation exposure. They concluded that associations have been weak and elevated risk occurred mainly in participants with high doses, exposed at young ages and in women.…”
Section: Discussionmentioning
confidence: 99%
“…Ron and Brenner29 summarised the evidence of benign thyroid diseases after radiation exposure. They concluded that associations have been weak and elevated risk occurred mainly in participants with high doses, exposed at young ages and in women.…”
Section: Discussionmentioning
confidence: 99%
“…Although a strong relationship exists between hypothyroidism and high-dose external or internal 131 I irradiation (30-80 Gy and Ͼ 185 MBq), the association is less for the low-dose ranges used in the current study. 48 Whether the subclinical hypothyroidism in the current animals is a consequence of RIT cannot be ruled out. However, histopathologic changes in the thyroid were not observed in any of the dogs treated with higher doses of 211 At; and taking the short half-life of 211 At into account, it is unlikely that the thyroid received a high enough dose to induce a state of deficiency.…”
Section: Durable Donor Engraftment 1135mentioning
confidence: 93%
“…2.07; 95% CI: 0.28–10.31) . Epidemiologic data on radiation risk of FA are sparse because it is difficult to distinguish adenoma from certain benign thyroid lesions and follicular carcinoma …”
Section: Discussionmentioning
confidence: 99%